Hybrid regulatory T cells: camouflaged architects of tumor immunity - Azimnasab-Sorkhabi, Parviz; Soltani-asl, Maryam; Kfoury Junior, Jose Roberto; Ansa-Addo, Ephraim A. (Frontiers in Immunology, 2025)
Distinct from conventional Foxp3+ regulatory T cells (Tregs), T-bet+ Tregs represent a stable subset of immunosuppressive T cells characterized by co-expression of the transcription factors (TFs) Foxp3 and T-bet. Given that Tregs were also reported to co-express Foxp3 together with effector T cell TFs such as GATA3, or RORγt, we propose the term hybrid Tregs (hTregs) to distinguish between these Tregs that co-express Foxp3 together with effector T cell TFs from conventional Foxp3+ Tregs. Therefore, this review will focus on hTreg cells, a specific subset of CD4+ T cells, and discuss the different types of hTregs with particular emphasis on T-bet+ hTregs. T-bet+ hTregs exhibit unique features including IFN-γ production, high expression of immune checkpoints (PD-1, CTLA-4, GITR, OX40, TIGIT), and chemokine receptors (CXCR3, CCR5). Through secretion of IL-10, TGF-β and IFN-γ, T-bet+ hTregs modulate both innate and adaptive immune responses within the tumor microenvironment (TME). Their high expression of CD73 contributes to adenosine-mediated immunosuppression, while CXCR3 and CCR5 facilitate their recruitment to inflammatory sites. T-bet+ hTregs were reported to accumulate in multiple human cancers, including lung, ovarian, and colorectal carcinomas. Despite these advancements, the function of hTregs in diseases such as cancer remains poorly understood, and requires further investigations. For instance, some studies suggest T-bet+ hTregs to be anti-inflammatory due to their production of IL-10, TGF-β, and superior suppressive capacity compared to conventional Tregs. Yet, other studies have reported that T-bet+ hTregs exhibit enhanced proinflammatory functions in colitis and other pathologies. We will then highlight current known mechanisms that promote the differentiation and functions of T-bet+ hTregs in cancer. Lastly, we will discuss the advancements and opportunities for therapeutic targeting of T-bet+ hTregs in cancer immunotherapy.